Pengaruh Potensi Pajak Daerah , Optimalisasi Pajak dan Insentif Pajak terhadap Realisasi Penerimaan Pendapatan Asli Daerah pada Badan Keuangan Kota Bukittinggi - Harmanto, Rudi; Khairul, Khairul (CV. ITTC INDONESIA, 2022)
This study aims to determine and analyze the effect of analyzing the potential effect of local taxes, analyzing the effect of tax optimization and analyzing the effect of tax incentives on the realization of local revenue receipts at the Bukittinggi City Finance Agency.This type of research is quantitative descriptive with the object of research being taxpayers and state civil servants at the Bukittinggi City Finance Agency. The data used are primary and secondary data. The population of this study is taxpayers and employees of the Financial Agency in the Bukittinggi City Financial Agency which consists of hotel taxpayers totaling 83 people, restaurants totaling 100 people and Finance Agency employees totaling 92 people. The results of this study prove that the Potential of Local Taxes has a positive and significant effect on the Realization of Regional Original Revenue, Tax Optimization has a positive but not significant effect on the Realization of Regional Original Revenues and Tax Incentives have a positive and significant effect on the Realization of Regional Original Revenues.